Short-term creatine supplementation changes protein metabolism signaling in hindlimb suspension - Marzuca-Nassr,G.N. (2019)
The effect of a short-term creatine supplementation on hindlimb suspension (HS)-induced muscle atrophy was investigated. Creatine monohydrate (5 g/kg b.w. per day) or placebo, divided in 2 daily doses, was given by oral gavage for 5 days. Rats were maintained in HS with dietary supplementation concomitantly for 5 days. Body weight, soleus and EDL muscle masses, and cross-sectional areas (CSA) of the muscle fibers were measured. Signaling pathways associated with skeletal muscle mass regulation (FST, MSTN, FAK, IGF-1, MGF, Akt, mTOR, atrogin-1, and MuRF1 expressions, and Akt, S6, GSK3B, and 4EBP1 proteins) were evaluated in the muscles. Soleus muscle exhibited more atrophy than the EDL muscle due to HS. Creatine supplementation attenuated the decrease of wet weight and increased p-4EBP1 protein in the EDL muscle of HS rats. Also, creatine increased mTOR and atrogin-1 expressions in the same muscle and condition. In the absence of HS, creatine supplementation increased FAK and decreased MGF expressions in the EDL muscle. Creatine attenuated the increase in FST expression due to HS in the soleus muscle. MuRF1 expression increased in the soleus muscle due to creatine supplementation in HS animals whereas atrogin-1 expression increased still further in this group compared with untreated HS rats. In conclusion, short-term creatine supplementation changed protein metabolism signaling in soleus and EDL muscles. However, creatine supplementation only slightly attenuated the mass loss of both muscles and did not prevent the CSA reduction and muscle strength decrease induced by HS for 5 days.